Simultaneous Estimation and Validation of Four Antiepileptic Drugs from Bulk and Formulations Using Reverse Phase HPLC (Brazilian Journal of Pharmaceutical Sciences, 2023)
Epilepsy is a disorder of the central nervous system, in which the nerve cell activity in the brain is disturbed causing seizures. The objective was to develop an RP-HPLC method for consistent simultaneous quantitation of four antiepileptic drugs Levetiracetam (LVT), Lamotrigine (LTG), Phenobarbital (PBT) and Phenytoin (PTY). An isocratic method was developed on C18 column in JASCO HPLC using 5 mM potassium phosphate buffer (pH 6) and acetonitrile as the mobile phase at a flow rate of 1ml/min and detected at 230 nm using UV detector. The mean retention time for LVT, LTG, PBT and PTY were found as 2.55, 3.55, 4.65 and 5.99 minutes respectively. The method was validated as per ICH guidelines and was found to be acceptable. The %RSD value was <2.0 % thus stating the developed method was precise for the drugs in the given range. The accuracy values were within 85-115% of the recovery range. The specificity of the method was evaluated by an assay of marketed formulation, and it showed a percent content between 90-110% w/w for all the four drugs. The proposed analytical method was simple, accurate and robust and was precisely able to resolve the four major antiepileptic drugs. Hence, the current method can be applied successfully for routine examination of these drugs.